2012
DOI: 10.1159/000342672
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Patients with Hematological Malignancy after Admission to the Intensive Care Unit

Abstract: Background: The admission of patients with malignancies to an intensive care unit (ICU) still remains a matter of substantial controversy. The identification of factors that potentially influence the patient outcome can help ICU professionals make appropriate decisions. Patients and Methods: 90 adult patients with hematological malignancy (leukemia 47.8%, high-grade lymphoma 50%) admitted to the ICU were analyzed retrospectively in this single-center study considering numerous variables with regard to their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…This is the first descriptive analysis in the US evaluating PBT patients with an unplanned admission to an ICU. Our ICU mortality rate of 19% was similar to two similar French studies of PBT patients (22–23%) [ 6 , 7 ], similar to patients with solid tumors (17–23%) [ 4 , 8 ], better than patients with hematologic malignancies (40–46%) [ 4 , 21 , 22 ] and within the range expected for general ICU patients (3.4–66.7%) [ 9–12 ]. In addition to similar ICU mortality, our most common reasons for admission were similar to the two prior studies conducted in France: seizures and respiratory failure [ 6 , 7 ].…”
Section: Discussionsupporting
confidence: 87%
“…This is the first descriptive analysis in the US evaluating PBT patients with an unplanned admission to an ICU. Our ICU mortality rate of 19% was similar to two similar French studies of PBT patients (22–23%) [ 6 , 7 ], similar to patients with solid tumors (17–23%) [ 4 , 8 ], better than patients with hematologic malignancies (40–46%) [ 4 , 21 , 22 ] and within the range expected for general ICU patients (3.4–66.7%) [ 9–12 ]. In addition to similar ICU mortality, our most common reasons for admission were similar to the two prior studies conducted in France: seizures and respiratory failure [ 6 , 7 ].…”
Section: Discussionsupporting
confidence: 87%
“…The early and short-term mortality rates for ICU admitted patients were high (cumulative mortality rates at 1 month 34% and at 6 months 53%). This is similar to previous data, which report a range of in-hospital mortality of 46-90% 1,[4][5][6][11][12][13][14][15][16][17][18][19][20][21][22] , with multi-organ dysfunction (illustrated by use of mechanical ventilation, vasopressor use, renal replacement therapy, significant liver enzyme elevation, high Acute Physiologic Assessment and Chronic Health Evaluation (APACHE) II, Sequential Organ Failure Assessment (SOFA), or Simplified Acute Physiology Score (SAPS) scores) being the most common predictor of death 1,[4][5][6][11][12][13][14][15][16][17][18][19][20][21][22] . This was further confirmed in larger studies including a literature review of observational studies encompassing 10,000 patients 23 , and a retrospective analysis of 7689 patients with hematologic malignancy admitted to the ICU 24 .…”
Section: Discussionsupporting
confidence: 92%
“…ICU morbidity and mortality remain an important issue for patients with hematologic malignancy. Although predictors of mortality in patients admitted to ICU with hematologic malignancy are well described 1,[4][5][6][11][12][13][14][15][16][17][18][19][20][21][22] , there is a paucity of evidence that identifies the predictors of ICU admission in this population, or predictors of survival in hospitalized patients with hematologic malignancies. Overall, during a period of 5.5 years, 19% of patients with hematologic malignancies admitted to our tertiary care hospital were admitted to an ICU at least once, with 47% of these admissions to a high acuity (versus step-down) ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al found SOFA scores, hypotension, and septic shock to be predictors of mortality in their multivariate analysis [ 17 ]. Sepsis, acute respiratory failure, high doses of catecholamines, renal replacement therapy, and high SAPS II scores were found to be predictive of mortality in multivariate analysis done by Horster et al in 2012 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%